The Impact of Human Resource Management Practices on Knowledge Sharing: The Case of Poro Bank - Aklamanu, Alphonse Mawusi Kwasi (My University, 2008)
The main aims of this study were to examine the extent to which human management practices facilitate and enhanced knowledge sharing, and how human resource management practices impact on knowledge sharing in a regional branch of a Finnish bank. The theoretical part of the study was based on the literature on human resource management practices and three socio-psychological theories perceived as having impact on knowledge sharing were discussed to provide a broader understanding of socio-psychological factors that affect individuals’ behaviour in knowledge sharing in the organisation. The case study part of the research analysed the findings of the study concerning the link between HRM practices, organisational culture, and socio-psychological determinants perceives as facilitating knowledge sharing. This study adopted a qualitative retrospective approach based on a single case study employing semi-structured interviews to examine the knowledge-sharing features of the regional branch of a Finnish commercial bank. Using theoretical concepts drawn from socio-psychological and HRM domain regarding knowledge sharing behaviour, this thesis demonstrated that shared language, weekly meeting, trust, team work, long-term employment, and promoting equality and fairness at the work place have facilitated knowledge sharing. Furthermore, the findings of this study revealed that in-house training, job rotation and fair promotion and compensation system have impacted on knowledge sharing at Poro Bank. In addition, the organisational culture of the Bank has also facilitated knowledge sharing at Poro Bank.
Keywords: Knowledge sharing; human resource management; social capital theory; social dilemma theory; organisational culture